Implementation of Hospital Health Promotion at PKU Muhammadiyah Wonosobo Hospital: A Qualitative Study - Kartina Catur Agung Suprapto; Sitti Nurdjannah; Lina Handayani (Jurnal EduHealth, 2023)
Management policy is the most significant hospital health promotion standard, and it also influences other standards. Health promotion in hospitals that is not implemented will cause problems for the community. Information that is not conveyed makes one's understanding and knowledge worse. Therefore, this study aims to evaluate of implementation of hospital health promotion in PKU Muhammadiyah Wonosobo Hospital. This qualitative research uses a case study design. As many as 7 respondents including officials, health workers, staff, patients, and families of patients have conducted in-depth interviews. According to the findings of this study, hospital health promotion at the institution in issue is poorly managed. Therefore, hospital policymakers must pay greater attention to preparing competent budgets and human resources to support maximum hospital health promotion.